Implementation of Discharge Planning in Hospital Inpatient Room by Nurses - Asmuji Asmuji; Faridah Faridah; Luh Titi Handayani (Jurnal Ners, 2018)
Introduction: Discharge planning is still become a problem for health services in hospital in-patient rooms. Discharge planning commonly is only done when the patients leave hospital by giving them an explanation about the content of the controlling card. Discharge planning is a routine activity that must be done by nurses in order to give information to the patients about their condition and any actions can or should be undertaken by them. In fact, the importance of discharge planning is not yet balanced, nor effectively applied in field. This research was conducted to find out about the implementation of discharge planning by nurses in one of the hospital in-patient rooms at the hospital of study.Methods: This research was a qualitative research study conducted with the phenomenological approach. The informants were 6 patients and 6 nurses in first, second and third class nursing wards. The instruments used in this research were the researchers themselves with interview guidance, field notes and a tape recorder. The data was collected through an in-depth interview.Results: There were three themes found through the analysis, which were 1) the information dimension involving room orientation, rights and obligations, and patient health problems as the sub-themes; 2) the understanding dimension with knowing and understanding the discharge planning as the sub-themes; 3) the implementation dimension with the time of implementation and content of discharge planning as the sub-themes.Discussion: Complete information given to the patients will bring about a positive impact, so then they can help themselves in relation to their curing time at home. A lack of and unclear information will bring about negative impacts such as mistakes when taking drugs, poor diet, neglecting activity while staying at home